Role of high-throughput sequencing in the diagnosis of cutaneous T-cell lymphoma. Issue 9 (10th April 2018) - Rea, Bryan; Haun, Paul; Emerson, Ryan; Vignali, Marissa; Farooqi, Midhat; Samimi, Sara; Elenitsas, Rosalie; Kirsch, Ilan; Bagg, Adam
Abstract : Aims: Substantial clinicopathological overlap exists between cutaneous T-cell lymphoma (CTCL) and benign conditions, leading to diagnostic difficulties. We sought to delineate the utility of high-throughput sequencing (HTS) across a spectrum of histological findings in CTCL and reactive mimics. Methods: One hundred skin biopsies obtained for clinical concern for CTCL were identified, comprising 25 cases each from four histological categories: 'definitive CTCL', 'atypical lymphoid infiltrate, concerning for CTCL', 'atypical lymphoid infiltrate, favour reactive' or 'reactive lymphoid infiltrate'. T-cell receptor gamma chain gene (TRG) PCR and T-cell receptor beta chain gene HTS were performed on both skin biopsy and concurrently collected peripheral blood; most peripheral blood samples were also analysed by flow cytometry. Results: Histologically defined CTCL specimens had significantly higher clonality scores and T-cell fractions via HTS than all other groups (all p<0.002 and p<0.03, respectively). HTS was more diagnostically specific than TRG PCR in skin (100% vs 88%), while diagnostic sensitivity (68% vs 72%) and accuracy (84% vs 80%) were similar. TRG PCR and flow cytometry performed on blood were the least diagnostically useful assays. Some identically sized peaks detected by TRG PCR in concurrent skin and peripheral blood specimens were non-identical by HTS analysis. Conclusions: HTS, by assessing both clonality and T-cell fractions in skin biopsies, is a powerful tool to aid in the diagnosis of CTCL. It is more specific than TRG PCR in distinguishing definitive CTCL from reactive and indeterminate histology. Identically sized peaks by TRG PCR, typically interpreted to be clonally related, are not always clonally identical by sequencing.